“Odd and Luna” – pedagogical fairy tale about otherness and being different - Sanecka, Anna (Journal of Education Culture and Society, 2020)
Aim. The aim of the article is to present the pedagogical potential of the puppet performance “Odd and Luna” staged in Wroclaw Puppet Theatre. The performance is interpreted from the philosophy of dialogue’s point of view, focused mainly on the philosophy of Polish philosopher Józef Tischner.Methods.The plot and the main theme of the performance – the otherness, loneliness and meeting the Other as a way of overcoming one’s own lack of self-confidence and fear of being different – are described and analysed. The contents of the performance are studied in order to find in its significant categories present in philosophy of dialogue: “the Other”, “the face”, “the meeting”, “the speech”/ “the word” and “the dialogue”Results and conclusion. The article shows that such difficult subject as otherness on the one hand and being different on the other, can be shown and discussed within a stage performance as a relatively easy way of transferring to the children the values and demands of social life like openness to differences, openness to dialogue and relations, willingness of meeting Other and building one’s own identity and self-confidence. Mentioned above characteristics seem quite important in Polish increasingly diversifying society.